Fractional powers approach of operators for abstract evolution equations of third order in time - Santos, Lucas Araújo (2020)
In this work we study third order linear evolution equations in time, in the sense of theory of strongly continuous one-parameter semigroups, and approximations them of fractional order via theory of the fractional powers of closed and densely de ned operator tand ype Balakrishnan formula. As applications, we present approximations of the Moore-Gibson-Thompson type equations with fractional damped. Mathematics Subject Classification 2010: 34A08, 47D06, 47D03.